Statistical optimization, kinetic modeling, and techno-economic analysis for the production of high molecular mass dextran using sugarcane industrial waste-molasses - Rahman, Sameeha Syed Abdul; Pasupathi, Saroja; Karuppiah, Sugumaran (Bioresource technology reports, 2024)
This study focuses on the transformation of industrial wastes to wealth by utilizing treated sugarcane molasses (TCM) to produce dextran. The fermentation conditions for maximum dextran production were initially optimized using central-composite design in shake-flasks. The highest titer of dextran (60.0 ± 2.0 g/L) was obtained with optimized variables of 150 g/L substrate (TCM), 12.8 g/L yeast extract, 39.8 g/L K2HPO4, and 48 h fermentation time. Then, the profiles of dextran production, TCM consumption, and microbial growth were fitted by kinetic models to obtain the following kinetic parameters: 0.35 h−1 maximum specific growth rate (μmax), 0.48 g dextran/g substrate yield coefficient (Yps), 0.07 maintenance coefficient (ms), and 10.73 g product/g cell growth-associated constant (α). For determining the scale-up factors, the fermentation conditions were replicated in a 3 L fermenter at various stirring speeds (50–250 rpm), and a scale-up strategy based on constant P/V was used to predict the power consumption (1.88–285.51 W) for a pilot-scale of 2000 L working volume fermenter at various stirring speeds (10.8–54 rpm). The dextran produced was characterized using gel permeation chromatography to determine the molecular mass variations (3–4000 kDa) with fermentation conditions. The rheological variations of fermentation broth at different stirring speeds were also studied and related to the molecular mass of the dextran produced. Techno-economic analysis for dextran production explored a gross margin of 22.65 %, a return on investment of 16.80 %, and a pay-back time of 5.95 years. [Display omitted] •Optimization of dextran production from sugarcane molasses through RSM-CCD approach•Logistic model gave a specific growth rate of 0.35 h-1•Identification of mixed growth associated products using Leudeking-Piret expression•Influence of agitation speed on yield, viscosity, and molecular mass of dextran•Net profit value of $ 16.24 million with 7625 tons of annual dextran production